Policy Simulation of Electricity-Based Vehicle Utilization in Indonesia (Electrified Vehicle - HEV, PHEV, BEV and FCEV) - Indra Chandra Setiawan (Automotive Experiences, 2019)
In the past few years, the energy consumption of the land transportation sector has increased considerably. One of the breakthroughs by the Government through Presidential Regulation No. 22/2017 concerning General Plan for National Energy (RUEN) is the use of electricity-based vehicles to reduce fuel consumption and achieve energy security. Successful policy making for emerging industries depends on two main factors: the adoption of scientific perspectives and accuracy to predict impacts. Therefore, this review aims to conduct a study of policy simulation methodologies related to the use of electric vehicles in Indonesia. Also, identification of the gaps and limitations of previous research is carried out and recommending an agenda for further research.